SANITASI PONOOK PESANTREN MATHLABUL ULUM 01 OESA JAMBU KECAMATAN LENTENG KABUPATEN SUMENEP TAHUN 2014 - Ulfatun Nushush; Suparlan .; Hadi Suryono (GEMA LINGKUNGAN KESEHATAN, 2014)
Basicsanitary condition in boarding schools is an effort to control physical environmental factorswhich may otherwise result in negative impacts on the health of the occupants and local people aroundthe boarding schools. One boarding school named "Mathlabul Ulum" do have some sanitary problems suchas dirty surrounding, dirty bathrooms and kitchens, and high density of its occupants. The purpose of thisresearch was to describe the basic sanitary condition in the boarding school that is located in desa Jambu,kecamatan Lenteng, kabupaten Sumenep in 2014.This was a descriptive study. The primary data included assessment results of the designatedforms, assessment results of respondent's action, as well as secondary data sources consisting of thenumber of students, the 10 main diseases, and number of sanitary facilities. Observation of hygienic andhealthy practices was carried out using simple random sampling that produce 78 respondents. Results ofthe study were tabulated and analyzed descriptively.Basic sanitation in "Mathlabul Ulum" boarding school did not satlsfv the criteria or requirementsrepresented with a score of 456 (46%) score. In terms of actions of there were ten respondents (13%)that. were classified as good in terms of hygienic and healthy behavior while 68 respondents (87%) wereclassified as poor.Therefore, it is suggested that the management of the boarding school exercise proper controlover cleanliness of every room. The head of health center agency in Sumenep District and the localprimary health centers inspect and control all of the boarding school present in Sumenep district,particularly the Mathlabul Ulum boarding school in desa Jambu, kecamatan Lenteng, kabupaten Sumenep.